Acoustic Scattering Cross Sections of Smart Obstacles: A Case Study (Communications in Computational Physics, 2011)
Acoustic scattering cross sections of smart furtive obstacles are studied anddiscussed. A smart furtive obstacle is an obstacle that, when hit by an incoming field,avoids detection through the use of a pressure current acting on its boundary. A highlyparallelizable algorithm for computing the acoustic scattering cross section of smartobstacles is developed. As a case study, this algorithm is applied to the (acoustic)scattering cross section of a "smart” (furtive) simplified version of the NASA spaceshuttle when hit by incoming time-harmonic plane waves, the wavelengths of whichare small compared to the characteristic dimensions of the shuttle. The solution to thisnumerically challenging scattering problem requires the solution of systems of linearequations with many unknowns and equations. Due to the sparsity of these systemsof equations, they can be stored and solved using affordable computing resources. Across section analysis of the simplified NASA space shuttle highlights three findings:i) the smart furtive obstacle reduces the magnitude of its cross section compared to thecross section of a corresponding "passive” obstacle; ii) several wave propagation directionsfail to satisfactorily respond to the smart strategy of the obstacle; iii) satisfactoryfurtive effects along all directions may only be obtained by using a pressure current ofconsiderable magnitude. Numerical experiments and virtual reality applications canbe found at the website:              http://www.ceri.uniroma1.it/ceri/zirilli/w7.